The Effect of Prenatal Gentle Yoga on Sleep Duration of Primigravida Pregnant Women - Oktaviana Manda Putri; Evita Widyawati; Poppy Farasari; Friska Oktaviana (CV. Global Health Science Group, 2025)
Sleep disturbances are common complaints among primigravida pregnant women due to physical, hormonal, and psychological changes during pregnancy. Inadequate sleep duration may negatively affect maternal health and fetal well-being, highlighting the need for safe and effective non-pharmacological interventions. This study aimed to examine the effect of prenatal gentle yoga on sleep duration among primigravida pregnant women in Tulungagung. A quantitative study with a one-group pretest–posttest design was conducted. The sample consisted of 53 primigravida pregnant women in the second and third trimesters who participated in a prenatal gentle yoga program, selected using a total sampling technique. Sleep duration was measured before and after the intervention using a questionnaire adapted from the Pittsburgh Sleep Quality Index (PSQI), which has been previously validated and demonstrated good reliability with a Cronbach’s alpha coefficient of >0.70. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that prior to the intervention, most participants had a sleep duration of less than five hours per night, whereas after receiving prenatal gentle yoga, nearly all participants experienced an increase in sleep duration to more than seven hours per night. Statistical analysis revealed a significant difference in sleep duration before and after the intervention (p < 0.05). In conclusion, prenatal gentle yoga has a significant effect on increasing sleep duration among primigravida pregnant women.